Enhancing Literacy Skills through a Creative 'Literacy Tree' Workshop in Maluku Tengah, Indonesia - Fransina Latumahina; Astria Duhumona; Astin Tupu; Nahdira Syaripudin; Budiyono Budiman; Fajar Ramadhan Rais; Ismail Angkotasan (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to promote literacy skills and creative thinking among elementary school students (SD Negeri 170, 36, and 336) in Assilulu, Maluku Tengah, through a workshop developing a 'Literacy Tree', a two-dimensional paper-based learning media. The low reading interest among Indonesians, with only 0.001 percent reading regularly according to UNESCO, highlighted the urgency of our intervention. Our methodology comprised imparting knowledge about creating a 'Literacy Tree', stimulating creativity, fostering aspirations, and enhancing mental, intellectual, and emotional spirit, thus simplifying the comprehension of complex materials for students. Results indicated that the workshop significantly engaged students, enhancing their creativity and understanding of knowledge. Therefore, we advocate for the 'Literacy Tree' workshop's incorporation into the curriculum, emphasizing its potential to foster creativity and boost literacy skills in a fun and engaging manner, and encourage further research on its long-term impacts and scalability in other educational contexts. This innovative approach has implications for Indonesia's literacy enhancement strategies and could potentially be applied globally to address similar educational challenges.Highlights: Literacy Tree fosters literacy and creativity. Our method simplifies complex materials. Workshops enhance literacy strategies worldwide. Keywords: Literacy skills, Creative learning, Literacy Tree Workshop, Elementary education, Indonesian school curriculum.